Odontogenic tumors: a retrospective study in a Brazilian population according to the 5th WHO classification and historic context of previous classifications - Fernandes, Carla Isabelly Rodrigues; Deusdará , Letícia Kariny Teles; Cáceres, Cinthia Veronica Bardález López de; Pontual , Maria Luiza dos Anjos; Carvalho, Elaine Judite de Amorim; Perez, Danyel Elias da Cruz; Castro , Jurema Freire Lisboa (Journal of Oral Diagnosis, 2025)
The World Health Organization (WHO) periodically updates the classification of head and neck lesions, including odontogenic tumors (OT). This study aimed to report the frequency of OT diagnosed in an oral pathology unit according to the latest WHO edition and describe the classifications’ historical context. All clinicopathological records and microscopic slides of OT specimens diagnosed between 2000 and 2024 were retrieved from the files of an oral pathology unit in Brazil. Diagnoses were re-assessed, and the tumors were classified following the 5th WHO Classification of head and neck tumors. A total of 153 cases were evaluated. OT were predominant in women (80 cases; 52.3%), and the patients were mostly diagnosed in the fourth decade of life. Most of OT belonged to the epithelial group. Conventional ameloblastoma (CA) was the most prevalent tumor (68 cases; 44.4%), followed by odontoma (48 cases; 31.4%). Two cases of CA were re-classified as adenoid ameloblastoma. Systems’ classifications of OT have been based on tooth growth phase, tumor histogenesis, biological behavior, and immunohistochemical and molecular analyses. The current edition did not describe any significant changes. We verified that OT are uncommon and that further classifications will rely on specific genetic and molecular profiles.